(untitled) (AL MUNAZHZHARAH, 2021)
The influence of parental divorce on the behavior of students which can affect the behavior and mentality of a student, this study aims to find out the importance of students who experience the above need more attention and need a more approach so they don’t feel less confident and feel inferior. Divorce in the family can affect behavior towards students. This study aims to determine the effect of parental divorce on the behavior of students. The type of research used is quantitative using a quantitative descriptive approach and the sample in this study is the students of the Kedunglo al-Munadhdhoroh Islamic boarding school as many as 62 respondents. With probability sampling sampling technique. The data collection technique used is a questionnaire (questionnaire) and documentation. While the technical retrieval of data analysis used in this study using validity test, reliability test, normality test, homogeneity test and hypothesis testing using 1-way ANOVA using SPSS 25 software for windows. From the discussion of the analysis, it can be concluded that the results of the data are as follows. From the results in the calculation of the hypothesis test Fcount > Ftable, the hypothesis H0 is rejected, H1 is accepted, it is known that the value of Fcount = 4.101 > Ftable = 4.00. It is known that Fcount is greater than Ftable, then there is an influence of parental divorce on the behavior of students, so it can be concluded that the influence of parental divorce on the behavior of students is very influential because parents do not communicate with their children, pay less attention to the desires and needs of children when they are in boarding houses and the consequences on behavior Children include often aloof, irritable and difficult to socialize in the cottage environment.